LEGAL REASONS FOR THE JUDGE'S BOARD OF JUDGES TO APPROVAL THE LAWSUIT FOR REVOCATION OF CHILD CURRICULUM RIGHTS WHICH HAS HAD PERMANENT LEGAL FORCE - Ilham Indra Mulya; Dwi Aryanti Ramadhani (RADJA PUBLIKA, 2026)
This study aims to analyze the legal reasons for filing a lawsuit for revocation of child custody rights after a final and binding decision and to analyze the legal considerations of the panel of judges in Decision Number 42/Pdt.G/2024/PA.Prob. This study uses a normative legal research method with a statute approach and a case approach. The legal materials used consist of primary, secondary, and tertiary legal materials which are analyzed qualitatively using a descriptive-analytical method. The results of the study indicate that the lawsuit for revocation of child custody rights after a final and binding decision does not conflict with the principle of ne bis in idem or the principle of legal certainty as long as it is based on changes in circumstances that affect the child's best interests. In addition, this study found that the Panel of Judges correctly accepted and examined the lawsuit by basing its considerations on changes in circumstances and protection of the child's best interests. However, in terms of the construction of the ratio decidendi in the decision, there is still room for strengthening, especially in linking the facts proven in court with the application of the principle of best interests of the child.